Technological progress and diffusion: Decomposing total factor productivity growth in Brazilian manufacturing - Armando Castelar Pinheiro (Institute for Applied Economic Research (ipea), 2015)
In this paper we estimate the rate of total factor productivity (TFP) growth in 80 sectors of Brazilian manufacturing industry and use production functions to decompose TFP growth into technological progress and changes in efficiency. We find that growth of TFP was caused, in most sectors, by technological progress (advances in the frontier production function). While parametric TFP change averaged 2.6% p. a. in the 1970-80 period, best practice TFP advanced at about 3.3% p.a., whereas efficiency declined annually at a rate of 0.7%. Technological progress was more important in the paper and printing (4.2% p. a.), construction (4.2% p. a.), and chemical (3.7% p. a.) complexes, and stayed below average for the textile and footwear (3.1% p. a.), metal-mechanic (3.0% p.a.) and agroindustrial (3.0% p. a.) complexes.
Keywords: 330